O conceito de educação política: uma revisão bibliográfica das concepções teóricas consolidadas na última década - Bastos Junior, José Carlos (Universidade Federal de São Carlos, 2022)
The present work has the general objective to investigate the theoretical conceptions referring to the concept of political education present in the literature in the field of Education and Applied Human/Social Sciences, given that the current context, marked by the proliferation of disinformation (fake news), the rise of extreme right and successive attacks on democracy and institutions, highlights the need to investigate how the construction of theories that focus on the understanding of the concept of political education have taken place. The methodology adopted was bibliographic research, carried out in a national theses and dissertations database (BDTD), Scielo Brasil database, CAPES Periodicals Portal and in the HistedBR Online Magazine, using the last decade as a time frame (2010-2021) and the selection of related terms via Education Thesauri and consultation of scientific literature. The theoretical perspective that guided the conceptual analysis is Historical-Dialectical Materialism, which guided the categorization of selected works into perspectives (critical and non-critical) and subcategories. The results obtained through a bibliographic survey revealed that there is a relatively small set of academic research on the discussion of political education and its application in the curriculum of Elementary and High School, reinforcing the need for new investigations of a practical nature (Case studies, surveys) to be undertaken, especially in the Initial Years, a stage in which there was a large gap.
The concept of political education: a bibliographic rewiew of theoretical conceptions consolidated in the last decade
Keywords: Educação política; Pedagogia socialista; Educação soviética; Letramento político; Socialização política; Political education; Socialist pedagogy; Soviet education; Political literacy; Political socialization; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO